La canción social latinoamericana en Calle 13. Un estudio desde la perspectiva histórica discursiva. (2020)
This research article presents the analysis of the linguistic resources, the discursive, and the rhetorical strategies present in the lyrics of Calle 13 in order to locate them within the tradition of the Latin American social song. For this, it is circumscribed to the discursive historical perspective, a theoretical-methodological approach which belongs to the multidisciplinary current of the CDA (Wodak, 2003; 2011). Following García Canclini (1977, 1990), the concept of Latin American social song is defined as a popular art form that belongs to Calle 13’s musical and lyrical proposal. The corpus of analysis consists of nine songs from this band, taken from its albums and collaborations. The work proposes categories of analysis like: semantic macrostructures, intertextuality and interdiscursivity, rhetorical figures and topoi. At the end, the researchers concluded thatCalle 13 participates in the Latin American social song, while its lyrics constitute a further possibility of exaltation of Latin American itself and of the appropriation of national and local cultural values. It is also a voice of resistance, denunciation, and anti-imperialist struggle.